A Bioinformatics Pipeline for the Analysis and Target Prediction of RNA Effectors in Bidirectional Communication During Plant–Microbe Interactions - Zanini, Silvia; Šečić, Ena; Jelonek, Lukas; Kogel, Karl-Heinz (Frontiers in Plant Science, 2018)
Small RNA molecules are key factors in the communication between hosts and their interacting pathogens, where they function as effectors that can modulate both host defence and microbial virulence/pathogenicity through a mechanism termed cross-kingdom RNA interference (ck-RNAi). Consistent with this recent knowledge, sRNAs and their double-stranded RNA precursor have been adopted to control diseases in crop plants, demonstrating a straight-forward application of the new findings to approach agricultural problems. Despite the great interest in natural ck-RNAi, it is astonishing to find just a few additional examples in the literature since the first report was published in 2013. One reason might be that the identification of small RNA effectors is hampered both by technical challenges and lack of routine bioinformatics application strategies. Here we suggest a practical procedure to find, characterize and validate small RNA effectors in plant-microbe interaction. The aim of this review is not to present and discuss all possible tools, but to give guidelines towards the best established software available for the analysis.